Effect of Amendments on Biocontrol Efficiency of Trichoderma spp. and its Subsequent Effect on Seedling Growth - Debnath, Anamika; Bhattacharya, Prateek Madhob; Roy, Ayon (International Journal of Bio-resource and Stress Management, 2012)
Use of microbes for environmentally safe plant disease management largely depends on antagonistic ability of the isolate, and Trichoderma spp. occupies a major domain in biocontrol research. An attempt was made to improve the bioefficacy of the Trichoderma isolate through chitin (0.5% and 1%) and ammonium sulphate (0.5%, 1% and 1.5%) as amendments in the synthetic medium at UBKV, Coochbehar, India during 2007-2009. Competitive saprophytic ability of the Trichoderma isolate recorded highest with 1% ammonium sulphate amendment. Trichoderma isolate showed higher chitinase activity with ammonium sulphate addition irrespective of dose. Ammonium sulphate addition also increased the plant growth promoting ability of the Trichoderma isolate. Chitin enhanced the bioefficacy of the Trichoderma isolate but it is not at par with ammonium sulphate and highest bioefficacy was found when the Trichoderma isolate was grown with 1% ammonium sulphate as reflected in the antagonism index value. In vivo trial was conducted with Trichoderma grown on amended and non-amended media with cowpea as test plant and Rhizoctonia solani as test pathogen. Reduction in pre-emergence damping off was recorded with addition of Trichoderma. Highest reduction of the disease was observed in chitin amendment. Vigor index was also further increased with addition of amendments